2006
DOI: 10.1523/jneurosci.3014-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 Signaling RegulatesDe NovoProtein Synthesis of κ Opioid Receptor by Facilitating Polysomal Partition of Its mRNA

Abstract: The expression of opioid receptor (KOR) is subjected to both transcriptional and posttranscriptional controls. We report that KOR translation is regulated by netrin-1 in primary neurons of dorsal root ganglion (DRG) and in P19 embryonal carcinoma cells. Without stimulation, a significant portion of KOR mRNA is maintained in a dormant state and partitions in the translationally inactive, postpolysomal fraction. During netrin-1 stimulation, which activates its downstream target focal adhesion kinase (FAK), KOR m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 28 publications
2
40
0
Order By: Relevance
“…Previously, we have found that most kor mRNA is repressed until it is stimulated for translation (11,34). It has also been suggested that mRNAs, during transport, are usually silenced by repressors (35)(36)(37).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previously, we have found that most kor mRNA is repressed until it is stimulated for translation (11,34). It has also been suggested that mRNAs, during transport, are usually silenced by repressors (35)(36)(37).…”
Section: Discussionmentioning
confidence: 89%
“…Using the opioid receptor (KOR) as a model, we have begun to uncover several posttranscriptional regulatory events important for the expression of KOR protein. These include alternative mRNA splicing, changing mRNA stability (10), localized translation (11), and mRNA transport (12,13) in neurons.…”
mentioning
confidence: 99%
“…All of these putative target mRNAs have been identified in the axons of invertebrates (Martin 2004;Crispino et al 2009) and vertebrates (Willis et al 2007;Taylor et al 2009;Vogelaar et al 2009). It is important to note that receptors and transmembrane proteins can be synthesized locally in axons (Spencer et al 2000;Bi et al 2006;Tsai et al 2006) and that functional receptors appear to be incorporated into the axolemma via an ER-and Golgi-dependent mechanism (Merianda et al 2009). Although attention has been focused on miRNAs that are relatively abundant or enriched in the axon in this report (Table 1), it is likely that low abundance miRNAs might also play an important role in the regulation of local translation and axonal function.…”
Section: Resultsmentioning
confidence: 99%
“…important switch to activate the silenced KOR mRNA for translation is the phosphorylation of Grb7 by Focal Adhesion Kinase (FAK), which is a downstream signal mediator for various growth factors such as Netrin and EGF (13)(14)(15). To determine the physiological function of KOR in the developing nervous system, we conducted preliminary experiments using primary DRG neurons dissected from the wild-type (WT) and KOR-null animals (16) to examine several developmental parameters and the sensitivity of the dissected DRG cultures to stimulation by potential growth factors.…”
mentioning
confidence: 99%
“…P19 cells and DRG neurons were cultured as described in ref. 13, with slight modification. To exclude extrinsic effects on KOR expression and axon extension, NGF and N2 supplements were excluded from the regular culture medium.…”
mentioning
confidence: 99%